Critical analysis of layer 2 network security in virtualised environments. (2016) - Bull, Ronny L.; Matthews, Jeanna N.
In this article, we explore whether layer 2 network attacks that work on physical switches apply to their virtualised counterparts by performing a systematic study across four major hypervisor environments - Open vSwitch, Citrix XenServer, Microsoft Hyper-V Server and VMware vSphere - in seven different virtual networking configurations. First, we use a malicious virtual machine to run a MAC flooding attack and evaluate the impact on co-resident virtual machines. We find that network performance is degraded on all platforms and that it is possible to eavesdrop on other client traffic passing over the same virtual network for Open vSwitch and Citrix XenServer. Second, we use a malicious virtual machine to run a rogue DHCP server and then run multiple DHCP attack scenarios. On all four platforms, co-resident virtual machines can be manipulated by providing them with incorrect or malicious network information.